Attack graph reachability: concept, analysis, challenges and issues. Issue 6 (June 2021) - Al-Araji, Zaid J; Ahmed, Sharifah Sakinah Syad; Abdullah, Raihana Syahirah; Mutlag, Ammar Awad; Raheem, Hayder Adil Abdul; Basri, Siti Rohanah Hasan
Abstract : An attack graph (AG) is an abstraction that represents the paths by which an attacker could break a security policy, leveraging interdependencies among discovered vulnerabilities. However, current AG implementations are inefficient on large-scale networks. The increase of the number of hosts in networks causes an increase in the time it takes to generate the AG, especially the calculation time and the complexity of determining reachability. An attack graph (AG) is an abstraction that represents the paths by which an attacker could break a security policy, leveraging interdependencies among discovered vulnerabilities. However, current AG implementations are inefficient on large-scale networks. The increase of the number of hosts in networks causes an increase in the time it takes to generate the AG, especially the calculation time and the complexity of determining reachability. In this article, the authors examine techniques that calculate the reachability using a matrix or a hyper-graph.